2016
DOI: 10.14257/astl.2016.131.07
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Job Characteristics on Social Workers’ Self-Efficacy

Abstract: Abstract. This study examines the effects of job characteristics affecting selfefficacy. The study collected survey data from 155 social workers working at general community welfare centers in Seoul. The averages of job characteristics are task identity (3.92), skill variety (3.62) and autonomy (3.57); and the averages of social workers' self-efficacy are client support efficacy, practice theory efficacy, practice skill efficacy, and research efficacy, in descending order. According to the results of hierarchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
1
3
1
Order By: Relevance
“…Contrary to studies that indicate that self-efficacy can act as a mediator of the relationship between job characteristics and job satisfaction (Choi, 2016;Judge et al, 2000;Wang & Netemeyer, 2002), our results indicated that self-efficacy was not related to job satisfaction when considering job characteristics variables. This result indicates that self-efficacy does not have a mediator role between work design characteristics and job satisfaction.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to studies that indicate that self-efficacy can act as a mediator of the relationship between job characteristics and job satisfaction (Choi, 2016;Judge et al, 2000;Wang & Netemeyer, 2002), our results indicated that self-efficacy was not related to job satisfaction when considering job characteristics variables. This result indicates that self-efficacy does not have a mediator role between work design characteristics and job satisfaction.…”
Section: Discussioncontrasting
confidence: 99%
“…Within this understanding framework, self-efficacy becomes a key factor since its effect on both workplace and psycho-social wellbeing has been demonstrated (Judge & Bono, 2001;Ventura, Salanova, & Llorens, 2015), which includes major variables such as job satisfaction, performance, work conditions, among others. Traditionally, it has been suggested that self-efficacy plays a mediating role in the relationship between work design and several work outcomes (e.g., Choi, 2016;Judge, Bono, & Locke, 2000;Wang & Netemeyer, 2002). However, Parker, Wall, and Cordery (2001) considered that selfefficacy can be an antecedent of work design -in the expanded model of work design developed by Humphrey, Nahrgang, and Morgeson (2007) they did not consider self-efficacy as a mediator.…”
mentioning
confidence: 99%
“…We identified 10 studies that targeted adult female patients; of these studies, four were published in 2010, two in 2011, two in 2012, one in 2014, and one in 2016. We confirmed that depression was related to Integration [ 14 ], Tilt [ 15 ], Symbols [ 15 , 16 , 18 , 19 ], Space usage [ 17 , 19 ], Depiction [ 16 , 18 ], Pressure [ 15 , 16 ], Color [ 17 , 20 ], and Line length [ 15 , 16 ]. Combining the literature and the results of the DDS test in this study, we confirmed that 9 elements, including Integration, Tilt, Symbols, Enclosure, Space usage, Depiction, Pressure, Color, Line length, were related to depression ( Table 3 ).…”
Section: Resultssupporting
confidence: 55%
“…We reviewed previous studies (published since 2010) [ 14 - 20 ] on the drawing styles of Korean women with depression, and discovered that the formative elements in the drawings reflected culture and environment, as well as gender-specific characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Self-efficacy affects both workplace and psycho-social wellbeing of teachers (Bargsted et al, 2019), which includes job satisfaction, performance and work conditions. Self-efficacy plays a mediating role in the relationship between work design and work outcomes (Choi, 2016). Teacher professional burnout is closely related to teacher perceived stress, which includes: i) emotional exhaustion, meaning being emotionally overextended and exhausted by one's work; ii) depersonalization, characterized by exhibiting negative, cynical attitudes toward others and treating people as objects; iii) experiencing negative assessment of the performance of teachers; iv) teachers being doubtful about making a difference in their job, and losing awareness of their personal competence (Draper et al, 2004;Zautra et al, 2002).…”
Section: Discussionmentioning
confidence: 99%